The effectiveness of product placement in a 60 second video and its influence towards consumer behaviour / Aiza Adriena Abdull Ropha - Abdull Ropha, Aiza Adriena (Faculty of Business and Management, 2018)
Marketers are constantly looking for alternatives to deliver the right message too the target market. Product placement has been one of the alternatives and has grown for decades that many companies have used in their marketing communication method. It has been established that viewers are starting to get annoyed by the commercial breaks in between television shows and before movies. Product placement offers a platform for companies to include their brands into the movies without irritating the viewers with pauses in between television shows and movies. There are many studies done by many researchers all over the world regarding the effectiveness of product placement. However, the results vary according to geographical location as viewers’ preferences vary according to many variables. This research project examines the relationship between the effectiveness of product placement that is measured in a 60 second video towards the independent variables including brand consciousness, plot integration and product prominence. In this study, the result shows that the general feedback towards product placement is positive for Kuala Lumpur citizen, although not strong enough. It’s proven that plot integration is the strongest variable to have impact on the effectiveness of product placement in a 60 second video according to the results derived from the SPSS data.